Zastosowanie miodu w rzymskiej medycynie weterynaryjnej - Bartnik, Agnieszka (Instytut Historyczny Uniwersytetu Wrocławskiego, 2019)
Ancient peoples were convinced that honey had therapeutic properties. It was used to treat people and animals. In veterinary practice, honey-based medicines were used mainly for ailing horses.